Added value in the context of research information systems. Issue 3 (4th July 2016) - Nabavi, Majid; Jeffery, Keith; Jamali, Hamid R.
Abstract : Purpose: – The purpose of this paper is to discuss added value in the context of current research information systems (CRISs) based on metadata enrichment. Design/methodology/approach: – This discussion paper uses literature review as well as analysis of CRISs specifications to discuss added value possibilities. Findings: – Added value of the CRISs is in their integration and interoperability with the same and similar information systems. Since metadata plays key roles in interoperability of information systems, therefore focussing on metadata-related issue can add considerable values to CRISs. Two types of metadata can be distinguished in every CRISs including macro- and micro-metadata. In terms of macro-metadata common European research information format (CERIF) by itself is an added value for CRIS because it draws a complete view of the research landscape including entities and their relations. CERIF metadata structure is designed in such a way that supports micro- and macro-metadata. Originality/value: – There is a lack of literature on adding value to research information systems especially CRIS and particularly how value can be added in CRISs still is an unanswered question. CRIS developers can use this paper as a road map to choose the most valuable strategy for adding value to their systems.